2013
DOI: 10.7150/ijms.6254
|View full text |Cite
|
Sign up to set email alerts
|

Sugammadex, a Neuromuscular Blockade Reversal Agent, Causes Neuronal Apoptosis in Primary Cultures

Abstract: Sugammadex, a γ-cyclodextrin that encapsulates selectively steroidal neuromuscular blocking agents, such as rocuronium or vecuronium, has changed the face of clinical neuromuscular pharmacology. Sugammadex allows a rapid reversal of muscle paralysis. Sugammadex appears to be safe and well tolerated. Its blood-brain barrier penetration is poor (< 3% in rats), and thus no relevant central nervous toxicity is expected. However the blood brain barrier permeability can be altered under different conditions (i.e. ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(44 citation statements)
references
References 38 publications
1
43
0
Order By: Relevance
“…In this study, we confirmed disruption of the BBB ultrastructure in neonatal mice exposed to sevoflurane. This study indicated that sugammadex passed through the BBB, which was disrupted by neonatal sevoflurane exposure, and that sugammadex induced neuronal apoptosis as seen in primary culture [4]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we confirmed disruption of the BBB ultrastructure in neonatal mice exposed to sevoflurane. This study indicated that sugammadex passed through the BBB, which was disrupted by neonatal sevoflurane exposure, and that sugammadex induced neuronal apoptosis as seen in primary culture [4]. …”
Section: Discussionmentioning
confidence: 99%
“…Palanca et al [4] reported that sugammadex altered cholesterol homeostasis. Long-term memory impairment must be examined in a future study because we previously showed that high levels of apoptosis soon after anesthesia cause long-term memory impairment in adults [14, 19].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a study of Palanca it was stated that SUG causes neuronal apoptosis in primary cultures [25]. Primary cultures of cortical neurons were prepared from the cerebral cortex of 14-15 day old rat fetuses (5 female rats to obtain fetuses).…”
Section: Discussionmentioning
confidence: 99%
“…However, one safety issue has been raised by Palanca et al who found that clinically relevant sugammadex concentrations in primary culture was associated with cortical neuron necrosis and cell death. 169 This may have potential implications for sugammadex use if used in patients where the blood brain barrier has been disrupted (trauma, ischemia, infections) or immature (neonates) and warrants further investigation.…”
Section: Safetymentioning
confidence: 99%